Analisis Kualitas Pengalaman Pengguna Sistem Pengelola Jurnal Menggunakan Metode User Experience Questionnaire - Ahmad Farisi; Mardi Wicaksana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
SIPENAMAS is a Research and Community Service System used by University MDP Lecturers to facilitate those who will submit and report research activities and community service. By using the UEQ method to measure the of the University MDP SIPENAMAS website. The purpose of the study was to determine and analyze the level of the University MDP SIPENAMAS website using the UEQ method. which consists of 6 variables, namely attractiveness, perpicuity, efficiency, dependability, stimulation, and novelty. The data collection process was carried out by distributing s to users of the University MDP SIPENAMAS Website, using a random sampling technique. In processing the data obtained using special software for the UEQ method. The results of the analysis with the UEQ are found that the value of the 6 scales, namely attractiveness 1.10, clarity 0.98, efficiency 0.88, accuracy 1.13, stimulation 0.92, and novelty 0.57 on the SIPENAMAS MDP website gets a score below average. Recommendations in this study are expected to provide consideration for improving on the SIPENAMAS MDP website.